Analisis Status Mutu Air Tanah Sekitar Tambak Udang di Desa Hadiwarno, Kecamatan Ngadirojo, Kabupaten Pacitan, Jawa Timur - Adam, Husnul Khotimah Dwi Putri; Widiarti, Ika Wahyuning; Wicaksono, Aditya Pandu; Irawan, Agus Bambang; Asrifah, Rr. Dina (Jurnal Lingkungan Kebumian Indonesia, 2023)
Hadiwarno Village is one of the regional villages in Pacitan Regency which has a large number of shrimp ponds of around 28.95 hectares. Shrimp ponds have been operating since 2015. Shrimp pond activities have the potential for liquid waste to seep into groundwater, requiring further processing. The purpose of this research was to determine the status of groundwater quality due to shrimp pond waste in the study area. The types of methods used in research are qualitative and quantitative methods. Data collection uses survey and mapping methods. Groundwater sampling using a systematic sampling method with an interval of 15 meters from the shrimp ponds. The data analysis method used is quantitative and qualitative data analysis methods for pollution indices, the relationship between chemical geophysical aspects, problems and impacts from shrimp pond waste. The results showed that the value of the status of water quality in the study area at the three sample points was included in the slightly polluted classification with a pollution index value of 2.1766 to 4.9625